Factors influencing entrepreneurial intentions of international and local students in Hungary - Ildikó Rudnák; Kíra Kollár; Jingjing Wu (Journal of Innovation and Entrepreneurship)
Abstract This study offers valuable insights for educational institutions by comparing the entrepreneurial intentions (EI) of international and local students in Hungary and analyzing the impact of entrepreneurial self-efficacy on their EI. A quantitative empirical approach was conducted to collect a total of 824 copies of electronic questionnaires from five universities in Hungary, which included valid responses from 345 international students and 309 local students. The data were analyzed using exploratory factor analysis, independent samples t tests, and hierarchical multiple regression analysis. In this study, entrepreneurial self-efficacy was examined through four components: operation and management capacity (OMC), relationship coordination capacity (RCC), risk tolerance capacity (RTC), and innovation and opportunity identification capacity (IOIC). The findings indicated no significant differences between entrepreneurial intentions of international and local students in Hungary. However, OMC and RTC were found to significantly influence the entrepreneurial intentions of both international and local students. In contrast, RCC did not show any significant impact on either group, while IOIC significantly affected only the entrepreneurial intentions of international students. To address these findings, universities should implement tailored workshops that focus on communication, teamwork, and networking to help bridge the gap between international and local students, as well as promote the generation of creative thinking and entrepreneurial engagement. The findings of this study have practical implications for improving the policy and practice of entrepreneurship education.